2019
DOI: 10.9734/jsrr/2019/v24i330155
|View full text |Cite
|
Sign up to set email alerts
|

Causal Linkage amongst Public Expenditure on Health, Health Status and Growth: New Empirical Evidence from Toda-Yamamoto Approach for Nigeria

Abstract: This study investigates the causal linkages amongst public expenditure on health, health status and economic growth in Nigeria using the Toda-Yamamoto technique. The choice of the Toda-Yamamoto approach is predicated on its simplicity and the ability to overcome the shortcomings inherent in the conventional causality procedures by producing more robust results through the estimation of the augmented VAR that guarantees the asymptotic distribution of the Wald statistic. To this end, the study collected annual t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 1 publication
3
6
0
Order By: Relevance
“…Olisakwe (2019) used the classical linear regression method over a period of 36 years and observed that increased government budgetary spending on the health sector inversely impacts economic growth in Nigeria. In the same line, Nwani and Kelikume (2019) also found similar findings as those by Olisakwe (2019). The study by Nwani and Kelikume (2019) employed the use of the Toda–Yamamoto analytic method to establish the causal connection between healthcare spending, health status, and GDP growth from 1981 to 2018.…”
Section: Literature Reviewsupporting
confidence: 82%
See 1 more Smart Citation
“…Olisakwe (2019) used the classical linear regression method over a period of 36 years and observed that increased government budgetary spending on the health sector inversely impacts economic growth in Nigeria. In the same line, Nwani and Kelikume (2019) also found similar findings as those by Olisakwe (2019). The study by Nwani and Kelikume (2019) employed the use of the Toda–Yamamoto analytic method to establish the causal connection between healthcare spending, health status, and GDP growth from 1981 to 2018.…”
Section: Literature Reviewsupporting
confidence: 82%
“…In the same line, Nwani and Kelikume (2019) also found similar findings as those by Olisakwe (2019). The study by Nwani and Kelikume (2019) employed the use of the Toda-Yamamoto analytic method to establish the causal connection between healthcare spending, health status, and GDP growth from 1981 to 2018. They confirmed the existence of an inverse non-interdependent nexus relating to public healthcare spending and economic expansion.…”
Section: Empirical Literature Reviewmentioning
confidence: 99%
“…On contrary to this, Olisakwe (2019) argued that an increase in budgetary allocation for health has negative outcomes on economic growth this was proven by extracting data from 1981 to 2017 in Nigeria using a classical linear regression technique to conduct the investigation. Nwani and Kelikume (2019) deducted the same conclusion as Olisakwe (2019) 3 | DATA, MODEL, AND METHOD…”
Section: Literature Reviewmentioning
confidence: 62%
“…The study revealed that health is a significant determinant of long-run economic growth in sub-Saharan African countries. Nwani and Kelikume (2019) investigated the linkage among public expenditure on health, health status and economic growth in Nigeria from 1981 to 2018. The results revealed that there existed a long-run association among public health expenditure, health status and economic growth.…”
Section: Review Of Literaturementioning
confidence: 99%